Psicanalisi freudiana e psicanalisi relazionale: teoria e pratica clinica a confronto - Meroni, Edoardo (Metapsychologica - rivista di psicanalisi freudiana, 2023)
This article aims to show the basic incompatibility that lays between the relational psychoanalytical theory and the Freudian one. Comparing the central ideas of both theories and approaches, the Freudian theory shows that it takes into account the mental phenomenon in a more complex way, although more explanatory. For example, in the Freudian theory the concept of relation cannot be considered as originating in the formation of the subject, but rather subordinated to the constitution of the subject’s identity and self-perception of it. According to Freud, internal drives and in particular those of self-preservation, which play no role in the relational theory, play instead a decisive role in the latter. The differences between the two approaches is also highlighted from a practical point of view. As proof, unlike the Freudian theory, in the relational theory the concept of countertransference has the function of being a cognitive instrument for the patient’s unconscious, instead of being perceived as an obstacle in the analytic process. The arbitrariness of this modification in the use of the countertransference is demonstrated. A critical comparison has carried out how rationally unjustified is to leave the Freudian doctrine behind, in favor of a type of modernization of the psychoanalytical technique, such as the relational one.